Develop the Inventory Management System of the Building Unit and Landscape Architecture, Nakhon Pathom Rajabhat University - Khamsuwan, Treechadaporn (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2024)
The purpose of this research is twofold: 1) to develop a material management system for the building and facilities unit of Nakhon Pathom Rajabhat University, and 2) to study satisfaction with the material management system among personnel and stakeholders. A questionnaire was used to collect data from a target group of 5 individuals who are involved in material procurement and related tasks. The data collected was analyzed using statistical methods such as frequency, percentage, mean, and standard deviation. The study discovered that the targeted group showed a great deal of satisfaction with the material management system that was created for the building and facilities unit of Nakhon Pathom Rajabhat University. The group was most satisfied with two areas in particular: the security system management, which had an average score of 4.80, and the completeness of the system with respect to the requirements, which had an average score of 4.56. The satisfaction levels were also high for the system usability evaluation and system duties evaluation, with average scores of 4.40 and 4.25, respectively. This indicates that the developed material management system has the highest level of security in operation and can fully support the work according to the requirements of the users and the research objectives of this study. Based on the survey and data analysis, there are recommendations for improving the efficiency of the organization's material management system. It is suggested to study a more diverse and comprehensive population to obtain reliable and diverse information that can support the material management system of other organizations with high volume of data and users effectively.